Resource allocation on agent meta-societies - Cunha, Alcino (1997)
This paper is concerned with the formalization of a automated contracting mechanism that enables a society of cooperative resource allocation agents to negotiate rationally in a self-interested meta-society. Such environments induce agents to adopt different social behaviors according to the negotiation partner. This problem may be solved by taking an economic perspective in all the decisions, namely, by using utility based agents, through the use of marginal utility calculations, and defining dynamically the market extent for a task. The risk attitude and reactivity of each agent can be parameterized in order to achieve different negotiation strategies. The framework presented in this paper can be applied in a wide variety of situations, ranging from electronic commerce on virtual economic markets, to load distribution problems.